Peran Teori Akuntansi Terhadap Sistem Pelaporan Keuangan Pada PT. Ramayana Lestari Sentosa - Putri Permata Sari; Tri Herlinda; Liana Liana (Jurnal Riset Akuntansi, 2024)
This article discusses the role of accounting theory in the financial reporting system in company PT. Ramayana Lestari Sentosa. Accounting theory has an important role in development of accounting and financial reporting systems in companies. This research using qualitative descriptive methods of secondary data at PT. Ramayana Lestari Sentosa. The results of this research indicate that the company has implemented accounting theory in its financial reporting system. However, there are several challenges and obstacles faced in the implementation of the accounting system, such as changes in regulations, limited human resources, use of technology, limited time and costs, and experiencing difficulties in processing data. By Therefore, companies must pay attention to these factors in developing the system better and integrated accounting. It is hoped that this article will provide insight and understanding a better understanding of the role of accounting theory in the development of accounting and reporting systems finances in the company.